Neuromuscular Taping in Diabetes Mellitus: A Narrative Review of Current Understanding and Potential Therapeutic Applications - Abhishek Sharma; Nidhi Sharma; Aksh Chahal (Journal of Diabetology)
Abstract Background: Diabetes Mellitus (DM) poses significant challenges, including peripheral neuropathy and impaired muscle function. Neuromuscular taping has emerged as a noninvasive therapeutic approach, potentially offering benefits in managing DM-related complications. Materials and Methods: A comprehensive literature search was conducted to identify relevant studies investigating the use of neuromuscular taping in individuals with DM. Key databases were explored using Boolean operators (AND, OR, etc.), and articles were selected based on predefined inclusion criteria. Results: The review identifies 22 relevant articles, with 8 specifically addressing NMT in DM. Out of these, 5 were randomized controlled trials, highlighting the research interest in assessing the effectiveness of NMT. The findings suggest that NMT may positively impact the Ankle Brachial Index, indicative of improved peripheral blood circulation and many other health-related parameters. Neuromuscular taping principles and application methods are outlined, providing a foundation for understanding its potential therapeutic effects. Discussion: The potential therapeutic mechanisms of neuromuscular taping are explored, emphasizing its influence on sensory feedback, muscle activation, and circulation. Safety considerations and the feasibility of integrating neuromuscular taping into comprehensive DM management are discussed. Conclusion: Neuromuscular taping holds promise as an adjunctive therapy for managing DM-related complications. This structured narrative review provides a comprehensive overview for health care limitations such as a lack of standardized protocols and heterogeneity in study designs are noted.